Integrated water resources management: From a complexity theory perspective (2017)
Taking into account the international literature on the subject, it is necessary to advance in terms of leading theoretical definitions to go beyond the existing theoretical and methodological currents of thought. Past research has approached the issues of water management in a fragmented way; that is to say, without considering the multiple interrelations with other natural resources such as the soil, fauna, plants, and human beings. This reveals the need for acknowledging the nature and complexity of water management by involving socioeconomic, cultural, governance, sustainability, ecological, geological and other concepts related to natural resources. The purpose of this paper is to show how, from a new approach named the time-concept, it is possible to represent things as interrelated complex phenomena experiencing constant changes (in development). Thus, it is aimed at proposing new conceptual water management alternatives that integrate the multiple relations between nature and culture, including the appropriation of water heritage. The central underlying assumption in the paper considers that comprehensive water management conceived from the integration of nature–culture relations would encourage a respect for the uniqueness of biophysical and social contexts (which are in constant transformation). This, in turn, would favour the protection of water resources as a heritage in all its manifestations on Earth. The consolidation of the relations between nature and culture is interpreted as an interaction that occurs between human beings and the environment (the biophysical environment); this happens through cultural practices related to the different forms of appropriation of water: use, improvement, respect, love and protection. The contribution of this research is centred on proposing an alternative approach to an integral water management model from a complexity perspective; it would lead to studying water-related subjects in an interrelated and progressive way. © 2017 WIT Press.